187k views
3 votes
If g (x) = 2x + 2, find g (a + h) - g (a).

1 Answer

5 votes

Answer: 2h

Step-by-step explanation:

1) Given: g (x) = 2x + 2, find g (a + h) - g (a)

2) First, replace x by a + h:

g(a + h) = 2 (a + h) + 2 = 2a + 2h + 2

3) Second, replace x by a:

g(a) = 2a + 2

4) Subtract g(a+h) - g(a)

2a + 2h + 2 - (2a + 2) = 2a + 2h + 2 - 2a - 2 = 2h

Answer: 2a

Additional explanation:

This operation is the first step the function known as derivative, since derivative is defined as:

g'(x) = limit when h → 0 of [g( x + h) - g(h)] / h

Since, you have shown that the numerator is 2h, the limit is 2h/h = 2.

And now you know that the derivative of g(x) = 2x + 2 is 2.

User Secumind
by
5.7k points